Berbagai Variabel yang Mempengaruhi Efektivitas Program Pendidikan dan Pelatihan - Prianto, Agus (Jurnal Aplikasi Manajemen, 2009)
This research investigates many factors which influence the effectiveness of training program. The hypothesis of this research are goal orientation, perceived organization support, training motivation, readiness for change, and self confidence would predict the effectiveness of training. Besides, this research also investigates many dimension of the latent variable. By using analyzer statistics, that is structural equation modeling (SEM), this research is successfully identify many dimension of goal orientation, perceived organization support, training motivation, readiness for change, self confidence, and the effectiveness of training. This research also reveals: (1) there is a direct relationship between goal orientation with self confidence and training motivation, (2) there is a direct relationship between perceived organizational support with, training motivation, readiness for change, and the effectiveness of training, (3) by intermediated training motivation and readiness for change, there is an indirect relationship between goal orientation with the effectiveness of training, (4) by intermediated training motivation and readiness for change, there is an indirect relationship between perceived organizational support with self confidence. In short, this research reveals that training program plays the vital role for improvement human resource in an organization.